Analysis of the effect of phototherapy on intestinal probiotics and metabolism in newborns with jaundice - Fan, Sainan; Zhang, Kun; Zhang, Jiahui; Zhang, Lei; Liu, Lixiao; Lv, Anping; Ma, Yanan; Fang, Xiaohui; Zheng, Fang; Wu, Zhimin; Zhang, Jinping (Frontiers in Pediatrics, 2022)
Background: In clinical practice, oral probiotics are often given to children with hyperbilirubinemia who receive phototherapy, but the exact mechanism of the action of the probiotics on hyperbilirubinemia remains unclear. Method Fifty newborns who needed phototherapy from June 2018 to June 2020 were selected as the study subjects, and five healthy newborns in the same period were used as controls to analyse the changes in probiotic bacteria in their faeces. Results 1. In the intestinal tracts of newborns, Bifidobacterium is the main probiotic strain, with a small amount of Lactobacillus. There were probiotic species changes in the neonatal intestinal microbiota after phototherapy for 24 hours and 48 hours. The amount of Bifidobacterium and Lactobacillus decreased significantly (P < 0.05). 2. A correlation analysis of probiotic species and bile acid metabolism indexes showed that Bifidobacterium was positively correlated with many metabolites (P < 0.05), such as chenodeoxycholic acid, hyodeoxycholic acid, cholic acid, allocholic acid and β-cholic acid. It was also negatively correlated with many metabolites (P < 0.05), such as glycocholic acid, sodium, sodium tudca and chenodeoxycholic acid. Lactobacillus was negatively correlated with metabolites (P<0.05) such as α-sodium cholate and β-cholic acid. 3. A correlation analysis between the changes in probiotics and intestinal short-chain fatty acid metabolites after phototherapy showed that acetic acid, butyric acid, caproic acid and propionic acid decreased and were significantly correlated with Bifidobacterium (P < 0.05). 4. After phototherapy, 17 metabolites changed significantly (P < 0.05). This correlated with many probiotics (P < 0.05). The significantly changed probiotics in this study showed a significant correlation with some intestinal metabolites (P < 0.05). Conclusion It was found that phototherapy can significantly affect the intestinal probiotic flora and the metabolic indicators of newborns, which may be an important reason for the side effects of phototherapy, and also provides the theoretical basis for the provision of probiotics to newborns with jaundice.